Regenerative potential of skeletal muscle in elite Greco-Roman wrestler - Kasperska, A.; Ostapiuk-Karolczuk, J.; Zurek, P.; Wolny, R.; Hubner-Wozniak, E.; Zembron-Lacny, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The process of skeletal muscle regeneration is due to the activation of satellite cells, which proliferate and differentiate to form new myotubes. In regeneration the key role play hydrogen peroxide, nitric oxide, cytokines and growth factors which may come from many sources like, muscles and/or motor nerves and inflammatory cells. During recovery, most of these molecules have been released and could be useful in assessment of muscle regeneration in athletes (Hawke and Garry, 2001). The purpose of the study was to estimate the regenerative potential of skeletal muscle in elite Greco-Roman wrestlers compared to non-athletes. Methods: Greco-Roman wrestlers, members of national team were observed during preparatory training period (pre-season January). In blood were measured concentrations of hydrogen peroxide (H2O2), nitric oxide (NO), pro-inflammatory cytokines (IL-1â, TNFá), hepatocyte growth factor (HGF), insulin-like growth factor (IGF-I), platelet-derived growth factor (PDGF-BB) and brain-derived neurotrophic factor (BDNF). Total creatine kinase (CK) activity was determined as a marker of muscle damage. Body composition were estimated using a bioelectrical impedance (Tanita, Japan). Healthy and untrained men made a reference group. Results: The H2O2 concentration was higher in non-athletes, opposite to NO that was higher in wrestlers. The positive correlations was observed between NO and BDNF (r=0.641, P<0.001). The level of TNFá was 7-fold higher in wrestlers. Athletes with very high values of IL-1â and TNFá demonstrated the low level of growth factors and delay in regeneration of damaged muscles. IGF-I, PDGF-BB and BDNF was increased in wrestlers, in opposite to HGF that was lower in wrestlers compared to non-athletes. Individual analysis of IGF-I, PDGF-BB and BDNF revealed significant changes in highly qualified wrestlers. The activity of CK in wrestlers was measured for three days after strenuous training. The negative correlation was between percentage changes of CK and IGF-I (r=-0.755, P<0.001). CK activity was even 4-9-fold elevated in wrestlers. Analysis of body mass showed that wrestlers have lower fat mass (FM) but free fat mass (FFM) was higher than in non-athletes. Discussion: We have concluded that wrestling training at high intensity has significant influence on growth factors and increase of hydrogen peroxide and nitric oxide. The release of pro-inflammatory cytokines and growth factors is related to athlete`s fitness level, and effects on skeletal muscle regeneration.